THE EFFECT OF COMPENSATION AND JOB SATISFACTION ON TURNOVER INTENTION AT PT CITRA INSANI GARDA SEMESTA (CIGS) - Anggraeni, Dea Tiara; Ridho, Ali; Sudari, Suci Ayu (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
This study aims to examine the impact of compensation and job satisfaction on turnover intention among employees at PT CIGS. Validity and reliability tests, instrument analysis such as normality test, heteroscedasticity test, and multicollinearity test, t-test, F-test, and multiple linear regression analysis are conducted to provide research results and statistical data assumptions. Hypothesis testing shows that compensation and job satisfaction have a negative effect on turnover intention. This study contributes to the academic field by enhancing the understanding of factors influencing employee turnover intention. Additionally, the results are expected to provide insights for company management in managing compensation and improving job satisfaction to reduce employee turnover.